An introduction to atmospheric radiation - Liou, Kuo-Nan (International geophysics series, 2002)
This Second Edition of An Introduction to Atmospheric Radiation has been extensively revised to address the fundamental study and quantitative measurement of the interactions of solar and terrestrial radiation with molecules, aerosols, and cloud particles in planetary atmospheres. It contains 70% new material, much of it stemming from the investigation of the atmospheric greenhouse effects of external radiative perturbations in climate systems, and the development of methodologies for inferring atmospheric and surface parameters by means of remote sensing. Liou's comprehensive treatment of the.